Degradation products of profenofos as identified by high-field FTICR mass spectrometry: Isotopic fine structure approach. Issue 1 (2nd January 2017) - Angthararuk, Dusit; Harir, Mourad; Schmitt-Kopplin, Philippe; Sutthivaiyakit, Somyote; Kettrup, Antonius; Sutthivaiyakit, Pakawadee
ABSTRACT: This study was performed to identify the degradation products of profenofos" a phenyl organothiophosphate insecticide" in raw water (RW) collected from the entry point of Metropolitan Water Works Authority "Bangkaen, Thailand" and ultrapure water (UPW) with and without TiO2 under simulated sunlight irradiation. Degradation of profenofos was followed with ultrahigh performance liquid chromatography (UHPLC) and follows pseudo first-order kinetic. Accordingly, high-field FTICR mass spectrometry coupled to an electrospray ionization source was used to reveal the degradation routes of profenofos and the isotopic fine structures (IFS) elucidations to approve the chemical structures of its degradation products. More degradation products were detected in UPW as compared to RW. Consequently, two main degradation pathways namely (i) interactive replacements of bromine and hydrogen by hydroxyl functional groups and (ii) rupture of PO, PS, CBr and CCl bonds were observed. None interactive replacement of chlorine by hydroxyl functional group was detected. Accordingly, mechanistical pathways of the main degradation products were established.